Use of embryonic stem cell-derived cardiomyocytes to study cardiotoxicity of bisphenol AF via the GPER/CAM/eNOS pathway. (28th February 2020) - Yang, Shoufei; Cheng, Wei; Li, Xiaolan; Liang, Fan; Zhou, Ren; Wang, Hui; Feng, Yan; Wang, Yan
Abstract: Bisphenol AF (BPAF) is a derivative of bisphenol A (BPA) that is widely used in fluorinated polymers, fluorinated rubber, electronic equipment, plastic optical fibers, etc. Studies have shown that BPAF exposure is associated with a number of diseases; however, little is known about the effects of BPAF on cardiomyocytes. We investigated the impact of chronic exposure to BPAF on cardiomyocytes derived from embryonic stem cells (ESCs). The present study showed that chronic exposure to various concentrations of BPAF (0, 8, 200 and 1000 ng/ml) induces cardiomyocyte hypertrophy. The ratios of microfilaments to mitochondrial length and the ratio of microfilaments to cell nuclei and MYH7b levels indicate that BPAF exposure alters the morphology of the cells and mitochondria. Furthermore, BPAF exposure at concentrations from 8 to 1000 ng/ml results in an increase in G protein-coupled estrogen receptor (GPER) expression. Additionally, our results suggest that these effects of BPAF mediate cardiomyocyte hypertrophy apparently due to an increase in the production of reactive nitrogen species (RNS) via an increase in endothelial NO synthase (eNOS). These results imply that ESC-based myocardial differentiation can be an excellent cellular model to study BPAF-induced cardiotoxicity at the cellular and molecular levels.